TRANSFER OF ULAYAT LAND OWNERSHIP RIGHTS ACCORDING TO LEGISLATION AND REGULATIONS IN INDONESIA - Roly Irvan; Bagio Kadaryanto (JCH (Jurnal Cendekia Hukum), 2021)
Ulayat land is a land with the members of the customary law community. This study aims to explain the transfer of customary land ownership rights according to the laws and regulations in Indonesia. The method used in this research is normative legal research, using a statutory approach. The results of the study explain that the recognition of ulayat rights is stipulated in the constitution of the State of Indonesia, namely Article 18B of the 1945 Constitution of the Republic of Indonesia admitts and reverences the customary community units and their traditional rights as long as they are alive and in accordance with with the development of society and the principles of the Unitary State of the Republic of Indonesia. Furthermore, Article 28 paragraph (3) of the 1945 Constitution of the Republic of Indonesia states that traditional cultural and community identities are respected in line with the development of times and civilizations. In the concept of national land law, there are three entities related to land status, namely state land, private land, and customary land, but in the concept of national forest law, only two forest statuses are recognized, namely state forest and private forest. In the concept of land acquisition for the public interest, indigenous peoples are not given the freedom to make decisions on development programs and investments made by the government on ulayat lands, for example toll road construction projects.